European Union Policy towards the Pacific Island States - Siekiera, Joanna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The article concerns the idea as well as the form of international cooperation between states and international organizations, illustrated by the example of the relationship between the European Union and the Pacific region. There is some useful literature on the subject but this needs be to completed. The influences of the world’s leaders collide on the Pacific Ocean, which gives this area primacy in geopolitical domination, slowly downgrading the Atlantic Community. The main purpose of the paper is, therefore, to research the possibilities and methods of legal and extrajudicial cooperation between two continents which are very distant from each other. This work underlines the difference between official policy, presented by the regional intergovernmental organizations, and the individual policies of member states, who are not tied down by Brussels politics and may maintain their own foreign relations.